PENGARUH CITRA PERUSAHAAN TERHADAP MINAT KONSUMEN INDUSTRI PERAWATAN KULIT PT. NATASHA SKIN CARE CABANG PEKANBARU - ", Muhardi; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in Natasha Skin Care Pekanbaru, the setting of the problem is how to influence the image of the skin care industry consumer interest. The purpose of this study was to determine the effect on the company's image indusrtri consumer interest Natasha Skin Care skin care Pekanbaru branch. The author uses descriptive quantitative analysis method and some theories about the company's image and interests. Indicators used in the independent variable is the personality, reputation, value, corporation identity and the dependent variable is the interest. Gathering data using questionnaires and interviews. The sample used was accidental sampling. Source of data used are primary data and secondary data. These results indicate that there is a strong relationship between the variables of corporate image to consumers.Keywords: corporate image, interests. The skin care industry.